Development and Usability Testing of an Online Tool for Intraoperative Assessment of Surgical Residents. (September 2013) - Flinn, J. T.; Miller, A.; Galloway, M.; Lin, K.; Watson, K.; Hellan, M.; Woods, R.; Cao, C. G. L.
Formal intraoperative assessments of surgical residents are often completed with pencil-and-paper forms, leading to a low rate of compliance with residency program guidelines. An online tool was developed for the evaluation of residents by attending physicians in the OR. Usability testing was conducted using two groups of users, one expert and the other naïve, using a newly developed variant of rapid iterative testing methodology called DONE-RITE. The tool was developed and refined over a series of rapid iterations where user interface and domain-specific usability issues were addressed by the naïve and expert user groups, respectively. The end result was the quick development of the online tool, which the expert users agreed was convenient to use in the OR and was likely to improve compliance with resident assessment guidelines.